Improving Yield Stability and Resiliency of Agronomic Production Systems in Southeast Kansas - G. F. Sassenrath; J. K. Farney; DeAnn Presley; C. Davis (Kansas Agricultural Experiment Station Research Reports, 2015)
Soil health is a critical determinant of crop performance. Soil physical, chemical, and biological properties can be modified through production practices such as tillage. Use of cover crops has been shown to benefit soil health and may improve productive capacity of soils. High rainfall and intense crop production practices limit the ability to implement cover crops in current production systems in southeast Kansas. This study explores potential management of cover crops and their contribution to soil health, crop productivity, and animal grazing.
Keywords: yield stability; southeast Kansas; production systems